منهج المواد الدراسية في تعليم اللغة العربية للناطقين بغيرها - Falah, Moch Fajarul; mukhlisah, mukhlisah; Rahman, Fadhlur (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2024)
The Arabic language holds an exceptional position in history, culture, and religion. Studying Arabic is not limited to understanding classical and contemporary literary works from the Arab world, but also provides access to knowledge and thought in various fields of science such as history and the sciences. Arabic also plays a crucial role in religion, as the Quran, the holy book of Islam, is written in Arabic.  Educational curriculum is a structured plan or program that includes a series of subjects and educational activities designed to achieve specific educational goals. It encompasses various aspects of the learning process, including learning objectives, teaching strategies, performance assessment, and evaluation. The primary goal of educational curriculum is to provide guidance and direction for the learning process so that students can achieve their full potential. Subject matter curriculum is an approach in curriculum design that emphasizes teaching subjects separately. In this model, each subject is taught as an independent and separate unit, without attempting to link the subjects together. Subject matter curriculum places greater emphasis on understanding concepts and facts in each discipline deeply.